Perkembangan Bioteknologi Masa Kini - Sumaryanto Sumaryanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
The modern products of biotechnology are, vaccine, interferon, interleukin, monoclonal antibody, new rice varieties, antibiotics, biological pesticides such as bacteria Bacillus thuringiensis which are active against specific insect species and their application through transgenic plants. There is a great difference in the products if compared with those of the conventional biotechnology, such as soy sauce, fish sauce, yoghurt, ethanol and tempe. Nowadays HIV/AIDS, pneumonia virus SARS (severe acute respiratory syndrome), genetic disorder, cloning, biological weapon such as anthrax from Bacillus anthraxis, are the kinds of several diseases, discoveries and conditions which look for development and clarification through biotechnology. It was shown in this paper some new biotechnology products, technology scope closely related to biotechnology and also the comparation of national priorities and strategy for developing of biotechnology in developed and developing countries.